Haplotype frequency distribution for 7 microsatellites in chromosome 8 and 11 in relation to the metabolic syndrome in four ethnic groups: Tehran Lipid and Glucose Study - Daneshpour, Maryam Sadat; Hosseinzadeh, Nima; Zarkesh, Maryam; Azizi, Fereidoun (Gene, 2012)
Different variants of haplotype frequencies may lead to various frequencies of the same variants in individuals with drug resistance and disease susceptibility at the population level. In this study, the haplotype frequencies of 4 STR loci including the D8S1132, D8S1779, D8S514 and D8S1743, and 3 STR loci including D11S1304, D11S1998 and D11S934 were investigated in 563 individuals of four Iranian ethnic groups in the capital city of Iran, Tehran. One hundred thirty subjects had the metabolic syndrome. Haplotype frequencies of all markers were calculated. There were significant differences in the haplotype frequencies in short and long alleles between the metabolic affected subjects and controls. In addition, haplotype frequencies were significant in the four ethnic groups in both chromosomes 8 and 11. Our findings show a relation between the short allele of D8S1743 in all related haplotype frequencies of subjects with metabolic syndrome. These findings may require more studies of some candidate genes, including the lipoprotein lipase gene, in this chromosomal region.